PROROTIPE ALARM PANIC BUTTON SYSTEM PADA WILAYAH HUKUM POLRES KOTA TANGERANG - Ahmad Roihan; Annas Rifa'i; Chandra Wijaya (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2018)
The development of informatics technology offers organizations the ease of providing a new solution for the improvement of the less ideal system. SPKT (Sentral Pelayanan Kepolisian Terpadu) is the place of public complaints service regarding assistance from the police when there is a crime orcriminalization, report etc. It needs innovation in public service report system to Polresta Tangerang to be more effective or efficient. In overcoming the problem Alarm Panic Button System can provide convenience to contact the Police when there is a crime. The design of the tool begins by creating a prototype tool with a circuit consisting of several components. Then the tool assembled and embedded the script by using software Arduino Uno v3.0 which is connected with SIM Module 800L GPRS GSM Micro Sim as the part of the circuit to send the message. The message will be sent directly to Polresta Tangerang. The purpose of the study can be to provide services with an access to facilitate the publicin informing and reporting criminal or other crimes to the police about events occurring at work, home or market. So the police are able to find out earlier about the incident and then take quick action to overcome it.